i-Herbs: An Expert System for Malaysian Herbs Identification Using Production Rules Approach - Roslina, Abd Hamid; Rahmah, Mokhtar; Nor Azhar, Ahmad; Fauziah, Zainuddin; Azma, Abdullah (American Scientific Publisher, 2018)
Expert System in identifying herbs, using Production Rules in the system will solve a problem of using conventional and manual procedures. By using physicals structure, defining herbs is tough. Identifying herbs by using collective intelligence from the public can lead to issues on trustworthiness. Rule based is derived from the rules for herbs expert knowledge domain. Thus, the system can learn from its experience by using factual knowledge based. The system has the ability to give the herb’s family name, scientific name and common name. Therefore, this system will help public to identify herbs easier. The result yields 75% of system outputs are properly matched to human knowledge. This system also can be implemented in others knowledge domain. In fact, the system can provide a list of herb benefits focusing herbs in Malaysia.